Implementasi Aktivitas Membuang Sampah Sesuai Jenisnya dalam Kedisiplinan pada Anak Usia 5-6 Tahun di Ra Fard Ahillah Sei Semayang Sunggal - Juwita Sari; Fauziah Nasution; Ahmad Syukri Sitorus (Inovasi Pendidikan dan Anak Usia Dini, 2025)
Early childhood is a child aged between 0 and 6 years. The early years are a special time for every child; this period is known as the "golden age" because of the rapid development of children during this period. The goal of early childhood education is to provide learning activities that can develop children's talents and skills and educate them about discipline by disposing of waste according to its type, not in the designated trash can. Early discipline is very important for children's adjustment in everyday life because it can help develop a healthy character that allows children to make their own decisions about what is and is not allowed to do in everyday situations. The purpose of this study is to improve a disciplined environment that encourages healthy child development so that children can grow into responsible, compassionate individuals who can learn from their mistakes. From the results of the study obtained using a descriptive qualitative approach method, it can be concluded that the purpose of daily activities is to help children develop discipline. Teachers often ask students to come to school ten minutes before the bell rings, shake hands, remind them to complete assignments on time, dress appropriately for school, and throw trash in the designated place.